The importance of Turkey for the energy security in the European Union - Pach-Gurgul, Agnieszka; Ulbrych, Marta (Journal of Public Governance, 2014)
This paper discusses the energy security of the European Union and the factors that determine it in an era of increasing demand for energy and the EU’s strong dependence on imported oil and gas from Russia. It points to the need to diversify sources and directions of energy supplies, and to use resources from the Caspian Sea areas, the Middle East, and North Africa, sent to the European Union countries through Turkey and bypassing Russia. Even though Turkey itself is not rich in energy resources, its transmission infrastructure may be a link between the European Union and the regions where more than 70% of the world’s oil and natural gas resources are located. That could change the position of Turkey as a candidate country in the European Union, and affect the cooperation with it in other fields. To transform Turkey into an energy corridor, it is necessary to build suitable transmission infrastructure that provides security of supply of raw materials to the EU countries.